Kewenangan Dewan Perwakilan Rakyat dalam Penggantian Hakim Konstitusi yang Berasal Dari Usulannya dalam Masa Jabatan - Alsyam, Alsyam (Universitas Ekasakti, 2023)
The precedent of dismissal and replacement of Constitutional Court Judge Aswanto during his term of office by the proposing body (DPR) is the first time this has occurred in the history of filling the position of Constitutional Court Judge in Indonesia. Does the DPR unilaterally have the authority to dismiss or...recall against Constitutional Judges originating from their proposals during their term of office. The research results explain thatLThe proposing body can renominate or replace the constitutional judge from his proposal during his term of office if the constitutional judge from his proposal is dismissed during his term of office by the President first at the request of the Chairman of the Constitutional Court based on the reasons stated in the Law on the Constitutional Court. However, the proposing institutions (DPR, Supreme Court and President) cannot unilaterally withdraw or recall constitutional judges based on their proposals.